Criminal Justice Response to Male and Female Victims of Domestic Violence - The Cases of Lucknow City of Uttar Pradesh (India) - Yadav, Brijendra Singh (International Journal of Psychosocial Rehabilitation, 2020)
Domestic Violence or Domestic abuse is defined as ‘An Incident or a pattern of incidents of controlling, coercive, threatening behavior, violence or abuse. It concerns people aged 16 or over who are or have been intimate partners or family members and it can happen regardless of your gender or sexuality. Domestic violence can include, but is not limited to the following types of abuse i.e. physical, psychological, emotional, sexual and financial. It also includes what is known as honor based violence, female genital mutilation and forced marriage. The Criminal Justice Response towards Male and Female in different way has always been a topic of debate for the criminal administration, Sociologists and Indian Judicial System. The present paper focuses attention towards the victimization of male by the criminal justice system and its ignorant and partial approach towards Male as Victims in general.